P178 Home remote-monitored auto-NIV: realistic provision and improved projected admission-free survival in patients with chronic hypercapnic COPD. (December 2018) - Toellner, H; McDowell, G; Burns, JE; Sumowski, M; Lowe, D; Carlin, C
Abstract : Background: The UK HOT-HMV-COPD study confirms benefit from home NIV in hypercapnic severe COPD patients. Home NIV provision presents clinical and service challenges, with repeated attendances and elective admission(s) unrealistic for COPD patients. 2-way remote monitoring and volume assured pressure support with auto-titrating EPAP (auto-NIV) modes offer prospects for realistic NIV optimisation and rationalised follow up. Methods: 46 patients with chronic hypercapnic COPD commenced remote-monitored home NIV in iVAPS-autoEPAP mode (Lumis, Airview, ResMed) between Feb-17 – Jan-18. Admission-free survival was compared with a cohort of COPD patients who survived an episode requiring acute-NIV, prior to home NIV service adoption. Results: Day-case NIV initiation was possible in 15/46 patients; 29 patients commenced NIV during index acute admission, including 7 patients as outreach to regional base hospitals. 36/46 continued NIV in volume-assured mode, 10 were switched to ST mode. Auto-EPAP component was discontinued in 18 patients. Follow up was individualised, typically requiring 6 data reviews, 2 telephone consultations and 1 remote prescription change. 15 patients required additional domiciliary nurse visit and 10 required additional day-case review to consolidate therapy. 11 patients were ultimately intolerant of home NIV despite all support; remote monitoring data justified ventilator retrieval. Median decrease in bicarbonate of 4.9 mmol/L (p<0.0151) and PCO2 2.2 kPa (p<0.032) confirmed control of hypoventilation. Median time to re-admission or death in patients who continued optimised home NIV was 28 weeks, vs 12 weeks in historical acute NIV cohort. Conclusions: Remote monitored auto-NIV facilitates treatment uptake, optimisation of home NIV and control of hypoventilation in patients with severe COPD. Admission-free survival improved from that projected from historical cohort, mirroring RCT outcomes.